Clinical features and prognosis of acute myocardial infarction due to coronary artery embolism. (25th November 2020) - Hata, R; Shimada, T; Shima, Y; Okabe, K; Ohya, M; Miura, K; Murai, R; Amano, H; Kubo, S; Tada, T; Tanaka, H; Fuku, Y; et al.
Abstract: Background: Coronary artery embolism (CE) is one of the important causes of acute coronary syndrome (ACS). The feature of CE is that angiographic evidence of coronary artery embolism and thrombosis without atherosclerotic components. However, the prevalence of CE remains unknown because of the diffifulty to diagnose in the acute settings. A recent retrospective analysis suggested that up to 3% of ACS cases may result from CE. Purpose: The aim of this study was to elucidate the prevalence, clinical features and long-term outcomes including all-cause and cardiac death. Methods: We analysed the consecutive 2695 patients with first AMI performed coronary intervention between January 2004 and July 2017. CE was diagnosed by clinical histories and angiographic findings. We retrospectively evaluated the clinical and lesion characteristics and outcomes including all-cause and cardiac death. Results: The prevalence of CE was 2.0% (n=55; CE group and n=2640; non-CE group), including 8 (15%) patients with multivessel CE. The CE group had higher average age (70.8±14.9 vs. 68.4±12.6, p<0.01), prevalence of female (54% vs. 27%, p<0.01), lower prevalence of smoking (34% vs. 62%, p<0.01). The common causes with CE were atrial fibrillation (47%), and malignant tumor (9%), and cardiomyopathy (5%), and patent foramen ovale (4%). Only 20% of patients with CE were treated with anti-coagulant therapy. The rate of distal infarction site (defined as #4, #8, #14–15) was significantly higher in CE group than non-CE group (54.0% vs. 4.9%, p<0.01). During median follow-up of 53.6 [32.6–77.3] months, CE and thromboembolism recurred in 5 patients (CE: 1 patient, stroke 4 patients). The 4-year incidence of all-cause death was significantly higher in the CE group, but cardiac death was not significantly different between the groups (28.8% vs. 14.8%, p=0.03; 12.8% vs. 5.1%, p=0.11). Conclusion: Compared with non-CE group, the prevalence of distal infarction site was significantly higher in the CE group, and the incidence of cardiac death is not significantly different. Funding Acknowledgement: Type of funding source: None